1989
DOI: 10.1007/bf02365549
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated hydrocarbons in North Sea whiting (Merlangius merlangus L.), and effects on reproduction. I. Tissue burden and hatching success

Abstract: Artificially inseminated eggs of feral North Sea whiting (Merlangius merlangus) were incubated in the laboratory in order to determine reproductive success. After incubation, two measures for reproductive success, total hatch and viable hatch, were determined and correlated with chlorinated hydrocarbon residues in the respective ovaries. From their specific toxicities and the sum of all determined chlorinated hydrocarbon contaminants, a contamination factor (CF) was calculated. Significant negative correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In both wild and captive "sheries, exposure of maturing females or direct exposure of eggs or developing embryos to environmental pollutants such as insecticides and organochlorine compounds a!ects egg and fry survival (Smith and Cole, 1973;Mauck et al, 1978;Westin et al, 1985;van Leeuwen et al, 1986;von Westernhagen et al, 1989;Matsui et al, 1992;Miller, 1993) as well as the viability of the spawned larvae, and may cause malformations or alterations in their development (Brooks et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…In both wild and captive "sheries, exposure of maturing females or direct exposure of eggs or developing embryos to environmental pollutants such as insecticides and organochlorine compounds a!ects egg and fry survival (Smith and Cole, 1973;Mauck et al, 1978;Westin et al, 1985;van Leeuwen et al, 1986;von Westernhagen et al, 1989;Matsui et al, 1992;Miller, 1993) as well as the viability of the spawned larvae, and may cause malformations or alterations in their development (Brooks et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that concentrations of chlorinated hydrocarbons in fish ovaries from the southern North Sea are responsible for an impairment of reproductive capacity due to increased prelarval mortality in whiting Merlangus merlangus (Westernhagen et al 1989), flounder Platichthys flesus and dab Limanda limanda (Cameron & Westernhagen unpubl.). Breeding experiments with M. merlangus also showed a positive relationship between anaphase aberrations in embryos and the contamination of PCB and DDE in parental gonads and liver (Dethlefsen et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Affected fish species include Atlantic salmon Salmo salar , Bylund & Lerche 1995, burbot Lota lota (SegerstrAle 1945, Pulliainen et al 1992, cod Gadus morhua (Westernhagen et al 1988, Larsson 1994, flounder Platichthys flesus (Westernhagen et al 1981), herring Clupea harengus (Hansen et al 1985), roach Rutilus rutilus, perch Perca fluviatilis, dace Leuciscus leuciscus and pike Esox lucius (Sandstrom et al 1988, Kards et al 1991, Pulliainen et al 1992, Luksiene & Sandstrom 1994, Wiklund & Bylund 1994, Pekkarinen 1995. Reproduction disorders in different fish species have also been observed in other sea areas such as the North Sea (Westernhagen et al 1989), Pacific Ocean (Hunter & Macewicz 1985, Spies & Rice 1988, Atlantic Ocean (Longwell et al 1992, Johnson et al 1994) and in freshwater areas (Norrgren et al 1994, Fisher et al 1995.…”
Section: Introductionmentioning
confidence: 99%